SOIL QUALITY INDEX ANALYSIS IN EFFORTS TO OVERCOME LAND DEGRADATION IN NGANJUK REGENCY - Dyah Nursita (Jurnal Sains dan Teknologi Mitigasi Bencana, 2020)
Soil quality is ability of soil to preserve the productivity of pants, preserve maintain water supplies, and support human activities. Soil quality assessment results can be used as a recommendation in addressing land degradation. The soil quality cannot be directly measured therefore physical, chemical and biological indicators collectively are determined which influence the soil quality called minimum data set (MDS). A study and experimental analysis was conducted in August - November, 2019. The descriptive study was done in some land units in Nganjuk Regency by measuring its soil index quality using Mausbach and Seybold (1998) criteria which has been modified by Partoyo (2005). The soil quality index was analyzed using function that represented most of the soil. The soil samples were taken by purposive sampling and the texture, volume weight, porosity, C-organic, pH, P-available, K-exchangeable, N-total and rooting depth were analyzed in laboratories. Soil quality index values ranged between 0-1. The higher index value indicates better quality. The analysis result of selected soil functions (MDS) and MDS scores were than summed to determine the value of the soil quality index (SQI). The study concludes that several land units in Ngluyu, Wilangan, and Tanjunganom Districts that had low soil quality (IKT = 0.2399 - 0.3869). Meanwhile, the land units in Bagor District have very good soil quality criteria (IKT = 0.8671). Keywords: soil quality index, land degradation, minimum data set, nganjuk.